Shadows and Cypress : Southern Ghost Stories - Brown, Alan, 1950 January 12- (Book collections on Project MUSE., 2000)
A bewitching convocation of Dixie's most frightening ghost tales From backwaters as dark as a cypress swamp to nooks as mysterious as a musty college library, southerners have conjured spirits and told ghost stories. Shadows and Cypress: Southern Ghost Stories is a Dixie seance that summons ghost tales from Alabama, Arkansas, Florida, Georgia, Kentucky, Louisiana, Mississippi, North Carolina, South Carolina, Tennessee, Texas, and Virginia. Collecting more than a dozen stories from each state, this book channels the South's entire panorama of creepy locales into one volume. The limestone caves.